Spatial transcriptomics in focal cortical dysplasia type IIb - Yujiao Wang; Yihe Wang; Linai Guo; Chunhao Shen; Yongjuan Fu; Penghu Wei; Yongzhi Shan; Qian Wu; Yue-Shan Piao; Guoguang Zhao (Acta Neuropathologica Communications)
Abstract Focal cortical dysplasia (FCD) type IIb (FCD IIb) is an epileptogenic malformation of the neocortex that is characterized by cortical dyslamination, dysmorphic neurons (DNs) and balloon cells (BCs). Approximately 30–60% of lesions are associated with brain somatic mutations in the mTOR pathway. Herein, we investigated the transcriptional changes around the DNs and BCs regions in freshly frozen brain samples from three patients with FCD IIb by using spatial transcriptomics. We demonstrated that the DNs region in a gene enrichment network enriched for the mTOR signalling pathway, autophagy and the ubiquitin‒proteasome system, additionally which are involved in regulating membrane potential, may contribute to epileptic discharge. Moreover, differential expression analysis further demonstrated stronger expression of components of the inflammatory response and complement activation in the BCs region. And the DNs and BCs regions exhibited common functional modules, including regulation of cell morphogenesis and developmental growth. Furthermore, the expression of representative proteins in the functional enrichment module mentioned above was increased in the lesions of FCD IIb, such as p62 in DNs and BCs, UCHL1 in DNs, and C3 and CLU in BCs, which was confirmed via immunohistochemistry. Collectively, we constructed a spatial map showing the potential effects and functions of the DNs and BCs regions at the transcriptomic level and generated publicly available data on human FCD IIb to facilitate future research on human epileptogenesis.